Você está na página 1de 30

N

2d sin θ =

θ

2θ

Kα, Kβ

3 GeV

2

ψ i

k 0 ω 0

ψ i = Ae i

k 0 · r0 t

ψ s

k

ψ s Ae iω 0 t e i

k 0 ·

r

+

ρr) e ikr

r

ρr)

rˆ (θ, φ)

ω 0

k 0 r k θ

2θ θ

R

e i

| r R| r

R

k 0 ·

ψ s e 0 t e i k 0 · R

e i

k 0 ·( r

R)

+ ρ(R) e ik| rR|

| r R|

r

k r R kr k

r

r ·

k = k 0

R = kr k · R

r

r

q = k k 0

θ

ψ s Ae iω 0 t e i

k 0 ·

r

+

ρ(R) e ik 0 riq · R

r

q

θ

q 2

k

2

0

=

=

= 2k

=

4k

2k

2 k 0 · k + k 2

2

0

2

0

2

0

2k

1 cos 2 θ + sin 2 θ

2

0

cos(2θ)

sin 2 θ

q = 2k 0 sinθ

θ = 0

ψ s Ae iω 0 t e ik 0 r

r

ˆ ρ(R)e iq · R d R

I( q) |ψ s | |ψ i |

2

2

ˆ ρ(R)e iq · R d R

2

= |ρ( q)| 2

ρ( q)

V ( r)

ρ ( q) =

m 2 ˆ

2π

e iq ·

r V ( r )d r ˆ e i

k 0 · r

V ( r )e i

k· r

r = k 0 |V | k

ρ

q

V ( r) = V α ( r r α )

α

k 0 |V | k

k 0 |V | k =

α

R α = r r α

ˆ e i

k 0 ·

r

V ( r r α )e i

k·

r r

k 0 |V | k

=

α

ˆ e i

k 0 ·( r α +

R α ) V ( R α )e i

k·( r α +

R α )

R

α

ˆ

α

α

e iq ·

R α V ( R α ) R

=

= V α ( q)e iq · r α

α

e iq ·

r

α

V ( q)

2 σ

∼ |V ( q)| 2 I( q)

I( q)

I( q) =

αα

e iq ·( R α R

α )

N I( q) N 2

α = α

αα α I( q) N N 2 I( q) I( q) N

S( q) = I( q)

N

S( q) = I( q)

V

S( q)

n = N/V

q k 0

In( q) ˆ ρ(

R)e iq ·

R d R ˆ ρ( R

)e iq · R

d R

R R + R

I( q) ˆ e iq ·

R

d R ˆ ρ( R)ρ( R + R )d R

P( R ) = ˆ ρ( R)ρ( R + R)d R

R

r

n( r) δ( r r α )

α

r α α

α n( r)

r α

n( r) r

ˆ n( r) r = N

n( r) r n = N/V

r

r r

n( r)

r

C nn ( r 1 , r 2 )

C nn ( r 1 , r 2 )

=

=

n( r 1 )n( r 2 )

δ( r 1 r α )δ( r 2 r α )

α,α

I( q)

=

αα

α )

e iq ·( r α r

=

ˆ ˆ
=

= n( q)n( q)

ˆ ˆ

e iq ·( r 1 r

2 ) δ( r 1 r α )δ( r 2 r α ) r 1 r

2

αα

e iq ·( r 1 r

2 ) n( r 1 )n( r 2 ) r 1 r

2

n( q) = ˆ e iq · r n( r) =

α

e iq · r α

C nn ( r 1 , r 2 ) I( q) C nn ( r 1 , r 2 )

r 1 r 2

| r 1 r 2 | → ∞

C nn ( r 1 , r

2

) | r 1 r

2 | n( r 1 ) n( r 2 )

S nn ( r 1 , r 2 )

 S nn ( r 1 , r 2 ) = C nn ( r 1 , r 2 ) − n( r 1 ) n( r 2 ) = [n( r 1 ) − n( r 1 ) ] [n( r 2 ) − n( r 2 ) ] = δn( r 1 )δn( r 2 )

r 1 r 2

| r 1 r 2 |

S nn ( r 1 , r 2 ) = δn( r 1 )δn( r 2 ) n( r 1 ) δ( r 1 r 2 )

V = ´ r

S nn ( q) =

V ˆ r 1 r

1

2 e iq ·( r 1 r

2 ) S nn ( r 1 r 2 )

S nn ( r 1 , r 2 )

V

I( q)

ˆ ˆ

=

ˆ ˆ
=

=

e iq ·( r 1

e iq ·( r 1 r

e q ·

r

2

) n( r 1 )n( r 2 ) r 1 r

2

2

) [S nn ( r 1 , r 2 ) + n( r 1 ) n( r 2 ) ] r 1 r

2

2

+

V S nn ( q)

ˆ

r n( r) r

n( q)

I( q) V 2 n( r) n

n( q) = ˆ e iq ·

r n( r) r = n V δ q, 0

S( q) = S nn ( q) + n 2 (2π) 3 δ( q)

V δ q, 0 = (2π) 3 δ( q)

q = 0

S( q) = 1

V

ˆ

r n( r) r

e iq ·

2

+

S nn ( q)

S nn ( q)

g( r 1 , r 2 )

 n( r 1 ) g( r 1 , r 2 ) n( r 2 ) ≡ =

α

=α

δ( r 1 r α )δ( r 2 r α )

α,α

δ( r 1 r α )δ( r 2 r α ) δ( r 1 r α )δ( r 2 r

α

)

=

n( r 1 )n( r 2 ) n( r 1 ) δ( r 1 r 2 )

g( r 1 , r 2 ) r 1

r 2

r 2

g( r 1 , r 2 )

 n 2 g( r 1 − r 2 ) = = =

g( r 1 , r 2 ) g( r 1 r 2 )

1

V ˆ r

1

α

=α

δ( r 1 r α )δ( r 2 r α )

V ˆ r 2 δ( r + r 2 r α )δ( r 2 r α )

α

=α

1

V

α

=α

α  

δ( r r α + r

r = r 1 r 2 α

r α r α α α

g( r) =

n

1

α

=0

δ( r r α + r 0

g( r)

r r

n r g( r)

g( r) r

ˆ n g( r) r

g( r)

=

=

N 1

1 N 1

1

g( r)

S( q)

=

=

=

+

V ˆ e iq ·( r 1 r

1

2 )

α

1

V

1

V

1

V

1

V

ˆ

ˆ

ˆ

ˆ

e iq ·( r 1 r

2 ) n( r 1 )n( r 2 ) r 1 r

2

2 )

αα

e iq ·( r 1 r

2 )

α

e iq ·( r 1 r

2 )

e iq ·( r 1 r

α

=α

δ( r 1 r α )δ( r 2 r α ) r 1 r

2

δ( r 1 r α )δ( r 2 r α ) r 1 r

2

δ( r 1 r α )δ( r 2 r α ) r 1 r 2

δ( r 1 r α )δ( r 2 r α ) r 1 r

2

=

=

1

V

n

α

ˆ

e iq ·

r δ( r r α ) r

2

r = r 1 r 2

V ˆ

1

2 )

e iq ·( r 1 r

α

=α

δ( r 1 r α )δ( r 2 r α ) r 1 r

2

=

=

1

V

1

V

ˆ

ˆ

e iq · r

e iq · r

α

=α

α =α

δ( r r α + r 2 )δ( r 2 r α ) r r

2

δ( r r α + r α ) r

= n ˆ

e iq · r

α

=0

δ( r r α + r 0 ) r

=

n 2 ˆ

e iq ·

r g( r) r

S( q) = n 1 + n ˆ e iq · r g( r) r

g( r) = 1

S( q) = n 1 + n (2π) 3 δ( q)

S nn ( q) = n

g( r) g(r) r = | r|

g(r)

 S( q) = = =

n 1 + n ˆ e iq · r g(r) r

n 1 + 2π n ˆ r 2 g(r) ˆ π exp (ikr cos θ) sin θ θ r

0

n 1 + 4π n ˆ

0

r 2 g(r) sin(kr) kr

r

S( q) S(q)

N

H =

N

α=1

p

2

α

2m α

+ V N ( r N )

r N N r α

δ( r r α ) = ´

´ δ( r r α ) exp(βV ( r N )) r

N

Z N (V, T)

Z N (V, T) = ˆ

ˆ exp(βV ( r N )) r N

n( r)

=

=

N

α=1

δ( r r α )

N!

(N 1)!

´

´ exp(βV ( r N )) r

N1

Z N (V, T)

ˆ n( r) r = N

α

=α

δ( r 1 r α )δ( r 2 r α ) =

N! (N 2)!

´

´ exp(βV ( r N )) r Z N (V, T)

N2

ˆ ˆ

α

=α

δ( r 1 r α )δ( r 2 r α ) r 1 r 2 = N (N 1)

E a E

E E a k = 2m(E E a )